Composite Biochar with Municipal Sewage Sludge Compost—A New Approach to Phytostabilization of PTE Industrially Contaminated Soils - Maja Radziemska; Mariusz Zygmunt Gusiatin; Zbigniew Mazur; Algirdas Radzevičius; Agnieszka Bęś; Raimondas Šadzevičius; Jiri Holatko; Midona Dapkienė; Inga Adamonytė; Martin Brtnicky (Energies, 2023)
The presence of potentially toxic elements (PTEs) in soils can upset the natural balance and increase the risk of PTE incorporation into the food chain. The use of composite biochar with municipal sewage sludge compost (MSSC/C) can be an effective way of both managing waste, such as sewage sludge, and providing an effective additive-supporting phytostabilization processes. The effectiveness of D. glomerata and MSSC/C in the technique of assisted phytostabilization of industrially contaminated soils was determined under the pot experiment conditions. The PTE contents in D. glomerata and the soil were determined using the spectrophotometric method. The addition of MSSC/C to PTE-contaminated soil contributed to an 18% increase in plant biomass and increased the soil pH by 1.67 units, with the PTE concentration being higher in the roots than in the above-ground parts of D. glomerata. The MSSC/C addition had the strongest effect on the reduction in Cd, Cr, and Ni contents in the soil following the completion of the experiment. The current study confirmed the effectiveness of MSSC/C in aiding the phytostabilization processes in PTE-contaminated soils.